Husband's social support and weight gain of pregnant mothers - Khoirunisa Nur Alfiana; Wafi Nur Muslihatun; Ana Kurniati (Poltekkes Kemenkes Yogyakarta, 2021)
Weight gain is declared normal when it is appropriate to recommendations, gaining weight outside the recommendations may affect women's pregnancy and there-to-be-born babies such as low birth weight, asphyxia, preeclampsia, blood sugar level increase, prolonged labor, and labor with cesarean section. This study aimed to find out the association between the husband's social support and the weight gain of pregnant mothers. This research is an observational analytical study with a cross-sectional design. This research was conducted in March 2021. The population of this research was the second and third-trimester pregnant mothers in the Public Health Center of Sentolo I. Sampling technique used purposive sampling and obtained 41 samples. Data collection used primary data. Analysis used frequency distribution and chi-square test. The result showed most of the respondents gained a normal amount of weight (51.2%). Amount of 58.5% of pregnant mother respondents received good social support from their husbands. There is an association between the husband's social support and weight gain of pregnant mothers with a p-value of 0.019. The proximity of association between the two variables is in a low category with a value of 0.345 and an RP value of 2.267 (95%, CI 1.030-4.989). the husband's social support has a relationship with the weight gain of pregnant women.